Associations of 5HTTLPR polymorphism with major depressive disorder and alcohol dependence: A systematic review and meta-analysis. (September 2016) - Oo, Khine Zin; Aung, Ye Kyaw; Jenkins, Mark A; Win, Aung Ko
Objective: The neurotransmitter serotonin is understood to control mood and drug response. Carrying a genetic variant in the serotonin transporter gene ( 5HTT ) may increase the risk of major depressive disorder and alcohol dependence. Previous estimates of the association of the S allele of 5HTTLPR polymorphism with major depressive disorder and alcohol dependence have been inconsistent. Methods: For the systematic review, we used PubMed MEDLINE and Discovery of The University of Melbourne to search for all relevant case-control studies investigating the associations of 5HTTLPR polymorphism with major depressive disorder and alcohol dependence. Summary odds ratios (OR) and their 95% confidence intervals (CI) were estimated. To investigate whether year of publication, study population or diagnostic criteria used were potential sources of heterogeneity, we performed meta-regression analyses. Publication bias was assessed using Funnel plots and Egger's statistical tests. Results: We included 23 studies of major depressive disorder without alcohol dependence containing 3392 cases and 5093 controls, and 11 studies of alcohol dependence without major depressive disorder containing 2079 cases and 2273 controls. The summary OR for homozygote carriers of the S allele of 5HTTLPR polymorphism compared with heterozygote and non-carriers combined (SS vs SL+LL genotype) was 1.33 (95% CI = [1.19, 1.48]) for major depressive disorder and 1.18 (95% CI = [1.01, 1.38]) for alcohol dependence. The summary OR per S allele of 5HTTLPR polymorphism was 1.16 (95% CI = [1.08, 1.23]) for major depressive disorder and 1.12 (95% CI = [1.01, 1.23]) for alcohol dependence. Meta-regression models showed that the associations did not substantially change after adjusting for year of publication, study population and diagnostic criteria used. There was no evidence for publication bias of the studies included in our meta-analysis. Conclusions: Our meta-analysis confirms that individuals with the homozygous S allele of 5HTTLPR polymorphism are at increased risks of major depressive disorder as well as alcohol dependence. Further studies are required to investigate the association between 5HTTLPR polymorphism and the comorbidity of major depressive disorder and alcohol dependence as well as gene × environmental interactions.